2022
DOI: 10.1021/acsami.2c07074
|View full text |Cite
|
Sign up to set email alerts
|

Metal–Acid Bifunctional Catalysts toward Tandem Reaction: One-Step Hydroalkylation of Benzene to Cyclohexylbenzene

Abstract: The one-step hydroalkylation of benzene to cyclohexylbenzene (CHB) is a technically challenging and economically interesting reaction with great industrial importance, where bifunctional catalysts play a crucial role in such a tandem reaction. In this work, we report H3PW12O40 (HPW) modified Ni nanoparticles (NPs) supported on mixed metal oxides (Ni/MMOs), which are featured by HPW species localized on the surface of Ni NPs (denoted as HPW-Ni/MMOs). The optimal catalyst (0.3HPW-Ni/MMOs) exhibits a satisfactory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 53 publications
0
9
0
Order By: Relevance
“…In situ CO adsorption FT-IR spectra (Figure a) were introduced to examine the structural details of Pt 1 /CoAlO x , Pt n /CoAlO x , and CoAlO x samples to gain further information about the dispersion and oxidation states of Pt. The absence of CO adsorption peaks on the CoAlO x sample suggests that the interaction only occurred between CO and Pt species, which is due to d−π* interaction on Pt 1 /CoAlO x and Pt n /CoAlO x . Typically, there are three characteristic adsorption peaks for CO on metallic Pt.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…In situ CO adsorption FT-IR spectra (Figure a) were introduced to examine the structural details of Pt 1 /CoAlO x , Pt n /CoAlO x , and CoAlO x samples to gain further information about the dispersion and oxidation states of Pt. The absence of CO adsorption peaks on the CoAlO x sample suggests that the interaction only occurred between CO and Pt species, which is due to d−π* interaction on Pt 1 /CoAlO x and Pt n /CoAlO x . Typically, there are three characteristic adsorption peaks for CO on metallic Pt.…”
Section: Resultsmentioning
confidence: 98%
“…As shown in the scanning electron microscopy (SEM) images (Figure 1b−e), the morphology of CoAlO x (Figure 1c), Pt 1 / CoAlO x (Figure 1d), and Pt n /CoAlO x (Figure 1e) maintains the original sheet-like hexagonal structure 27 of the CoAl-LDHs (Figure 1b) precursor. 24,25 High-resolution transmission electron microscopy (HR-TEM) measurement of Pt The dispersion state of Pt species was imaged intuitively through aberration-correction high-angle annular dark-field scanning transmission electron microscopy (AC-HAADF-STEM). 29 AC-HAADF-STEM images of Pt 1 /CoAlO x (Figure 1n,o) show that several evenly distributed bright spots (highlighted by the yellow circle) represent individual Pt atoms loading on the CoAlO x support, without any evidence for the presence of Pt clusters or nanoparticles, revealing the atomically dispersed nature of Pt.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Therefore, a hydrogen pressure of 1.5 MPa was chosen. Our previous study demonstrated that a semicontinuous procedure allows for the process-reinforced conversion of benzene with optimum hydrogen pressure . Herein, in contrast to the traditional one-step reaction process, an intensification mode was used via repeatedly injecting 0.5 MPa of H 2 in three stages (Figure S4), which shows a much higher CHB yield of 45.1% (Figure e), which is the top level compared with previously reported studies (Table S2).…”
Section: Results and Discussionmentioning
confidence: 99%
“…However, the interaction between metal and acid sites would notably affect the metallicity or acidity, thereby changing the capacity of benzene hydrogenation or benzene alkylation with CHE. For instance, our previous study demonstrated that electron transfer between metal and acid sites facilitates the formation and desorption of intermediate (CHE), which is favorable for the enhancement of catalytic behavior . However, fundamental research on electronic and geometrical configurations of “metal–acid” interfacial catalysts with adjustable reactivity is yet to be established in this field.…”
Section: Introductionmentioning
confidence: 99%
“…Due to its excellent physical and chemical properties, cyclohexylbenzene (CHB), an important chemical, has been widely used as an additive in lithium-ion secondary batteries, , an intermediate for the synthesis of liquid crystal materials, , and an additive in diesel fuels, , More importantly, the oxidation of CHB to benzylic hydroperoxide followed by a cleavage process can produce two valuable phenol and cyclohexanone chemicals, which may be utilized for the production of resins, bisphenol A, ε-caprolactam, and nylon . Different from the traditional Hock process involving the cumene oxidation to produce phenol, such an attractive route for the coproduction of phenol and cyclohexanone effectively solves the formation of excessive acetone. Owing to its high added-value and great potential for industrial applications, the large-scale production of CHB is highly desired. Commonly, CHB may be mainly synthesized via partial hydrogenation of biphenyl, , hydroalkylation of benzene, and direct alkylation of benzene with cyclohexene (CHE). , However, high-cost feed-stocks (biphenyl and CHE) are needed in the biphenyl hydrogenation route, while the direct alkylation route requires the addition of hazardous acid catalysts (i.e., aluminum chloride, sulfuric acid), in addition to low CHB selectivity in most cases (around 44%).…”
Section: Introductionmentioning
confidence: 99%